دراسة مستوى القلق اللغوي لدى الطلاب المتخصصين في اللّغة العربيّة بوصفها لغة أجنبيّة: الجامعة الإسلاميَّة العالميّة في ماليزيا نموذجا = Studying the level of linguistic anxiety among students specializing in Arabic language as a foreign language: The International Islamic University in Malaysia is a model - Eltingari, Salih Mahgoub Mohamed; Mohammed Jamel, Hossain (Faculty of Languages at Al-Madinah International University The Journal headquarters Malaysia., 2017)
يهدف هذا البحث إلى دراسة مستوى القلق اللُّغويّ لدى طلاب اللغة العربيّة في كُليتي معارف الوحي والعلوم الإنسانيّة، و كلية اللُّغات والإدارة- الجامعة الإسلامية العالمية في ماليزيا. وتتكون عينة الدراسة من 120 طالباً، 60 طالباً وطالبة من كل مجموعة. وقد وُزع عليهم استبيان خاصّ بظاهرة القلق اللُّغويّ، ثمَّ تمت عملية التحليل باستخدام برنامج Spss. وقد أظهرت النتائج أنَّ مستوى القلق اللغويّ عموماً لدى أفراد المجموعتين معتدل. وبَيَّنت النتائج أنَّ طلاب كليّة معارف الوحي أكثر قلقاً من زملائهم في كلية اللُّغات والإدارة ، وأنَّ أكبر مصدر للقلق اللغوي عند المجموعتين هو الخوف من التقويم السلبيّ . ولم تظهر الدراسة أي فرق ذي دلالة إحصائية في المجموعتين على مستوى النوع، والسنة الدراسية = This research aims to study the level of language anxiety among Arabic language students in the Kulliyyah of Islamic Revealed Knowledge and Human Sciences and the kulliyyah of Languages and Management of the International Islamic University Malaysia. The study sample consists of 120 students, divided into two groups, with each group consisting of 60 students. A questionnaire on language anxiety phenomenon was distributed among them and it was later analyzed using SPSS program. The results revealed that the level of language anxiety among the two groups is generally moderate. The results further stated that the students of the Kulliyyah of Islamic Revealed Knowledge and Human Sciences are more anxious than their colleagues in the kulliyyah of Languages and Management and the main source of language anxiety among the two groups is the fear of negative evaluation. The study did not expose any statistically significant differences in the two groups, in terms of gender, and year of study.